Dukungan Sosial dan Faktor Lain Yang Mempengaruhi Kualitas Hidup Wanita Dengan HIV/AIDS - Ganisia, Ainun; Fathiyyah, Nurul; Imeldawati, Rakhmalia; Kwarta, Cityta Putri (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
People with HIV/AIDS not only need medication to reduce physical discomfort, but also need social support to overcome psychological anxiety and restlessness. Social support is critical in maintaining good physical and mental health. This study aims to analyze the social support status of women with HIV/AIDS and explore other factors that affect their quality of life in Kecamatan Patrang, Kabupaten Jember. The research method used was cross-sectional with convenience sampling and data collection through questionnaires with SSRS (Social Support Rating Scale) within three months from March to May 2025, with a sample of 92 women with HIV/AIDS. It is known that there is a significant relationship between emotional support (p = 0.01) and assessment support (p = 0.03), as well as other factors such as the duration of ARV therapy (p = 0.03), with the quality of life of women with HIV/AIDS. These findings are expected to provide a basis for interventions, including the formation of peer-support groups, counseling programs focused on strengthening self-esteem, and training for families and communities to provide appreciation and respect to women with HIV/AIDS, which ultimately improves their health and quality of life.